Interdisciplinary connections to special education key related professionals involved - Obiakor, Festus E.; Bakken, Jeffrey P. (Bingley, U.K. : Emerald, 2015)
This two-part volume addresses the specific area of interdisciplinary connections within special education research. Special education has transformed as a result of legislation, new trends and current research investigations. Currently, there is no comprehensive resource that effectively covers these advances. Continuing the approach of part a, part b allows readers to follow interdisciplinary connections within special education as it relates to the roles of audiologists, surgeons, vision specialists and school nurses.
The role of the school nurse in special education / Kelly Schwend, Maureen Cluskey -- The role of art therapists in maximizing the mental health and potential of learners with special needs / Gaelynn P. Wolf Bordonaro, Laura Cherry, Jessica Stallings -- The role of physical therapists in advancing special education / Brenda Pratt, Melissa L. Peterson -- Role of speech-language pathologists in special education / Rita L. Bailey -- The role of special music educators and music therapists in assisting exceptional learners / Kimberly McCord -- Role of adapted physical education specialists / Deborah Garrahy -- Roles of various professionals related to the education of deaf/hard of hearing students / Christina M. Borders ... [et al.] -- Roles of nutritionists/dieticians in assisting exceptional learner / Patrick A. Grant, Nia A. Grant -- Role of specialists in working with learners with swallowing problems / Ruth Renee Hannibal -- Role of audiologists in special services / Lindsay Bondurant -- Role of vision specialists in special services / Stacy M. Kelly.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Special education; Interdisciplinary approach in education